Formulasi dan Uji Mutu Fisik Sediaan Pasta Gigi Herbal Ekstrak Temu Kunci (Boesenbergia pandurata Roxb) : Formulation and Physical Quality of Temu Kunci (Boesenbergia pandurata Roxb) as Toothpaste - Reza Alfian Ardianto; Cikra Ikhda Nur Hamida Safitri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Dental caries is one of the oral and dental problems in Indonesia. One of the causes of dental caries is the accumulation of dental plaque which is caused by food residue that sticks to the teeth and undergoes fermentation by the bacteria Streptococcus mutans. Temu Kunci (Boesenbergia pandurata Roxb) is one of Indonesia's native plants which contains flavonoids, tannins and saponins which can inhibit bacterial growth. The purpose of this study was to formulate the extract of temu Kunci (Boesenbergia pandurata Roxb) into a toothpaste preparation and the physical quality of these preparations. The key extract was obtained by maceration method using 96% ethanol as a solvent. Divided into several toothpaste preparations made with the concentration of extract of temu Kunci (Boesenbergia pandurata Roxb) FI 2%, FII 4%, FIII 6% with uniform toothpaste. Evaluation of dental preparations including homogeneity, organoleptic, pH, dispersibility and foam height tests. The test results of the three formulations of dental preparations showed that the three formulations were homogeneous, there was no organoleptic change, the pH range of toothpaste from 6.5 to 8.0 which fulfilled the pH requirements of toothpaste according to SNI 12-3524-1995 were 4.5 - 10, 5, the spreadability test of 6.5 to 8.0 cm, and the test of the height range of the foam from 6.6 to 8.3 cm.